Identification and prevalence of gastro-intestinal parasites among preschoolers aged 2-5 years old of Barangay 871, Zone 95, Kahilom 1, Pandacan, Manila - Asuncion, Grace C. 4 0 16; 5 (2005)
u
Thesis: (B.S. Biology)-Pamantasan ng Lungsod ng Maynila, 2005.
Keywords: 2 -- 0; 6; 20; 20; 2